Effects οf Yoga οn cancer patients: Secondary analysis οf Systematic Reviews/Meta-Analyses - Dimos Mastrogiannis; Anna Bitha (Ene, 2016)
Introduction: Western medicine's model has been enriched with alternative management and treatment methods. Yoga is a technique that incorporates physical exercises, breathing methods, meditation and relaxation which has been proposed to have positive effects on cancer patients. Aim: The aim of the present study is to critically review findings of systematic reviews/meta-analyses that are available in the international literature, regarding the effects of yoga on cancer patients. Methodology: Literature review was performed in five (5) databases: PubMed, Scopus, EMBASE, Web of Science and Cochrane Database of systematic Reviews. Authors adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analysis model in order to perform a critical review of the existing literature. Methodological assessment of papers under review was performed according to criteria of the Assessment of Multiple Systematic Reviews instrument. Inclusion criteria were the English language, research undertaken in adults and evaluation of effects of yoga as the primary intervention. Results: Although there is a lack of guidelines regarding the assessment of systematic reviews using the above mentioned instruments, 16 papers were included in the present study. Findings are confounding, even though there is evidence supporting the use of yoga in certain types of cancer. Specifically, improvements in quality of life and psychological wellbeing, anxiety, however, not pain reduction, have been reported in women suffering from breast cancer, however, no statistically significant effect has been documented in patients with haematological malignancies. Conclusions: The majority of studies about the effects of yoga on quality of life, fatigue, sleep quality, anxiety, and depression have small samples. There is a trend towards an overall quality of life improvement, nonetheless, the lack of sufficiently powered randomized controlled trials prevents the extraction of a safe conclusion about the efficacy of yoga in various cancer types and caution must be exercised by patients practicing yoga.